The Impact of Balanced Nutrition Education on Efforts to Prevent Stunting in Early Childhood - Andini Andini; Nurhayati Nurhayati; Sita Awalunisah; Durrotunnisa Durrotunnisa (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
This study aims to examine the impact of balanced nutrition education on stunting prevention efforts among early childhood learners in a Kindergarten setting. A mixed-methods approach was employed, integrating both qualitative and quantitative data to obtain comprehensive and reliable findings. The research subjects consisted of 15 children, including 5 boys and 10 girls. Data were collected through observation, questionnaires, interviews, and documentation, and analyzed using complementary qualitative and quantitative techniques. The results show that the overall achievement of balanced nutritional eating patterns reached 100%. Furthermore, the average score of children’s balanced nutrition eating behavior was 41.5%, categorized as “developing as expected” (BSH). These findings indicate that balanced nutrition education has a significant positive effect on stunting prevention efforts among early childhood learners aged 4–6 years in the Kindergarten context. The study suggests that early and consistent nutrition education should be integrated into school programs as well as family involvement activities to strengthen stunting prevention initiatives. Future research is recommended to include larger participant groups and utilize longitudinal approaches to examine long-term changes in children’s nutritional behaviors.